Ensino de Leitura na Linguística de Bloomfield e na Análise Comportamental de Skinner - Conceição, Djenane Brasil da (2015)
In a literate society like ours there are many advantages for both the individual and for the community in knowing how to read and write. Brazil's high illiteracy rates are well known, and eradicating functional illiteracy is a major ethical and political goal that studies and researches can help to reach. The present dissertation is an attempt to advance in this direction. We conducted a comparative analysis of the concept of reading and the method for teaching to read from the viewpoints of Leonard loomfield's structural linguistics and of B. F. Skinner's behavioral analysis. We worked on representative texts about the concept of reading and teaching to read by these two scholars. In behavior analysis, as a result of the findings of this research, we went beyond Skinner's texts, and entered the field of errorless learning. Leonard Bloomfield (1887-1949), one of the most important linguists of the twentieth century, was a behaviorist and influenced many aspects of B. F. Skinner’s work. In the 1930s Bloomfield developed a method for teaching reading, which culminated in the publication of “Let’s Read” in 1961. B. F. Skinner (1904-1990), the founder of behavior analysis, has been considered by many as the most prominent psychologist of the twentieth century. In the 1950s Skinner published "Verbal Behavior" (1957/1992), in which he addressed the study of language conceived as verbal behavior. Bloomfield considered the basic repertoire of reading as alphabetic habit, which consists in emitting vocal verbal responses corresponding to the printed text, a concept that is compatible with the design of Skinner's concept of textual (one of the units of analysis of verbal behavior). Both Bloomfield and Skinner considered the basic repertoire of reading, the alphabetic habit or textual behavior, as a prerequisite for reading comprehension. Teaching grapheme-phoneme correspondences as an essential part of a reading instruction program was advocated by Bloomfield and is nowadays widely accepted by researchers in the field of reading instruction. The fundamental principle that guides Bloomfield's reading instruction method is the systematic organization of the words presented for reading, based on the degree of regularity of grapheme-phoneme correspondences, from the alphabetic principle to reaching correspondences that deviate far from this principle. The basic teaching procedure is to present pairs of words that contrast in just one or a few letters. This procedure is compatible with differential reinforcement of responses in the presence of specific stimuli procedures used in establishing discrimination in Skinner's behavioral analysis. In addition, we identified in Bloomfield's reading instruction method principles of programmed instruction, which Skinner formulated in the 1950s. For example, requiring the learner to present at least one active response in every step of teaching, reinforcing correct answers immediately after their emission and preparing teaching materials in a gradual progression to enhance the learner's performance in every step of the teaching program. We identified that in Bloomfield's method he advocated errorless learning or learning with few errors, an element that appears in Skinner's behavioral analysis. We concluded that Bloomfield and Skinner's reading concepts are very similar and that Bloomfield's reading instruction method is compatible with behavioral analytical teaching procedures. Bloomfield designed a behavioral reading instruction method, advocated errorless learning or with a minimum of errors and attributed the emission of wrong answers by the learner to teaching method, as supported by the field of errorless learning. It should not be considered that Bloomfield's reading instruction method has actually been tested. Skinner's behavior analysis can contribute to refinements in Bloomfield's reading instruction method, for example, by systematizing the use of extrinsic reinforcers. The adaptation of Bloomfield's reading instruction method to the Portuguese language and its systematic combination with principles and procedures of behavior analysis require the collaborative work of linguists and behavior analysts (at least) and would have great potential, as shown by our analysis, towards solving the problem of Brazil's high rates of functional illiteracy.